Mesoproterozoic rifting and Pan-African continental collision in SE India: evidence from the Khariar alkaline complex - Upadhyay, D.; Raith, M.; Mezger, K.; Bhattacharya, A.; Kinny, Peter (Springer-Verlag, 2006)
The suture zone between the Bhandara craton and the granulite-facies rocks of the Eastern Ghats Province in SE India contains a number of deformed alkaline and tholeiitic intrusives. The Khariar alkaline complex is one of the several occurrences which intruded in the Mesoproterozoic (1,48017 Ma, 2r) and was deformed during the Pan-African tectonothermal event. The geochemical signatures indicate a rift-related setting for the magmatic activity. The nepheline syenite parent magma may have been produced by in-mantle fractionation of clinopyroxene and Ti-rich amphibole from a basanitic primary magma derived from an enriched spinel lherzolite mantle source in the sub-continental lithosphere. Geochemical variations in the Khariar alkaline suite can be modeled by the fractionation of clinopyroxene, amphibole, titanite, zircon, apatite and allanite. The Mesoproterozoic alkaline magmatism at Khariar marks the initiation of a NE-SW rift which formed several craton margin basins and opened an ocean towards the south. The sediments of the cratogenic basins and the Eastern Ghats Province were deposited in these rift-related basins. A K-Ar age of 1,33053 Ma from glauconites in sandstone suggests that the NW-SE trending Godavari-Pranhita graben formed at approximately the same time as the rift at the craton margin. If the two are related, the Godavari-Pranhita graben may represent the failed arm of a rift system in which the NE-SW arm was the active segment. The granulite-facies deformation and metamorphism of the Eastern Ghats Province sediments may be related to an episode of Grenvillian basin inversion. The Mesoproterozoic rifting and Grenvillian basin closure may thus represent two well-defined parts of a Wilson cycle i.e. the opening and closure of an ocean. The Khariar and other alkaline bodies were, however, deformed during a Pan-African collisional event associated with the westward thrusting of the Eastern Ghats Province granulites over the cratonic foreland.